2012
DOI: 10.2500/ajra.2012.26.3806
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 Gene Polymorphisms in Egyptian Patients with Allergic Diseases

Abstract: This preliminary study indicates that the studied polymorphisms do not confer susceptibility to allergy in Egyptian patients but may be related to the disease phenotype. However, the role of IL-18 in allergy may be too complex to be reflected in a simple association study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
(72 reference statements)
0
14
0
Order By: Relevance
“…The studies identified and their main characteristics were summarized in Table 1. Of the 21 case-control studies included, an array of allergic diseases including AA [31–40], AD [41–45], AR [10, 46], drug allergy [47, 48], and other types [49, 50] was involved. Of all studies included, 12 studies were conducted in Asian populations [31, 33, 36, 37, 39, 40, 4348], while 9 studies were performed in Caucasian populations [10, 32, 34, 35, 38, 41, 42, 49, 50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies identified and their main characteristics were summarized in Table 1. Of the 21 case-control studies included, an array of allergic diseases including AA [31–40], AD [41–45], AR [10, 46], drug allergy [47, 48], and other types [49, 50] was involved. Of all studies included, 12 studies were conducted in Asian populations [31, 33, 36, 37, 39, 40, 4348], while 9 studies were performed in Caucasian populations [10, 32, 34, 35, 38, 41, 42, 49, 50].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 21 case-control studies included, an array of allergic diseases including AA [31–40], AD [41–45], AR [10, 46], drug allergy [47, 48], and other types [49, 50] was involved. Of all studies included, 12 studies were conducted in Asian populations [31, 33, 36, 37, 39, 40, 4348], while 9 studies were performed in Caucasian populations [10, 32, 34, 35, 38, 41, 42, 49, 50]. There were 16 studies concerning IL-18 −607C/A [10, 31, 32, 35–40, 44–50] and 19 studies concerning −137G/C [10, 3137, 39–45, 4749].…”
Section: Resultsmentioning
confidence: 99%
“…AR is an inflammatory disease of the nasal mucosa induced by an immunoglobulin E (Helbling et al, 2014)-mediated reaction in allergen-sensitized individuals. It has been reported that numerous loci and candidate genes show an association with AR (Gaddam et al, 2012;Genuneit et al, 2009;Ibrahim et al, 2012;Tomazic et al, 2014). In spite of that, the molecular mechanisms underlying the development of AR have not been completely determined.…”
Section: Introductionmentioning
confidence: 94%
“…Figure 1 outlines the study selection process in a PRIS-MA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses)-sanctioned flowchart. Initial search resulted in 20 citations, followed by a series of omissions that eventually yielded 8 articles for inclusion [35][36][37][38][39][40][41][42]. Of the 8 included articles, 6 [35,[38][39][40][41][42] were not included in the previous meta-analysis on the same topic [21].…”
Section: Meta-analysismentioning
confidence: 99%